Hair cell-specific Myo15 promoter-mediated gene therapy rescues hearing in DFNB9 mouse model - Hui Wang; MengZhao Xun; Honghai Tang; Jingjing Zhao; Shaowei Hu; Longlong Zhang; Jun Lv; Daqi Wang; Yuxin Chen; Jianping Liu; Geng-lin Li; Wuqing Wang; et al. (Elsevier, 2024)
Adeno-associated viral (AAV) vectors are increasingly used as vehicles for gene delivery to treat hearing loss. However, lack of specificity of the transgene expression may lead to overexpression of the transgene in nontarget tissues. In this study, we evaluated the expression efficiency and specificity of transgene delivered by AAV-PHP.eB under the inner ear sensory cell-specific Myo15 promoter. Compared with the ubiquitous CAG promoter, the Myo15 promoter initiates efficient expression of the GFP fluorescence reporter in hair cells, while minimizing non-specific expression in other cell types of the inner ear and CNS. Furthermore, using the Myo15 promoter, we constructed an AAV-mediated therapeutic system with the coding sequence of OTOF gene. After inner ear injection, we observed apparent hearing recovery in Otof −/− mice, highly efficient expression of exogenous otoferlin, and significant improvement in the exocytosis function of inner hair cells. Overall, our results indicate that gene therapy mediated by the hair cell-specific Myo15 promoter has potential clinical application for the treatment of autosomal recessive deafness and yet for other hereditary hearing loss related to dysfunction of hair cells.